Taxonomy of the Genus Porella (Porellaceae, Marchantiophyta) on the Korean Peninsula - Hyun Min Bum; Seung Jin Park; Narae Yun; Vadim A. Bakalin; Seung Se Choi (Plants)
This paper provides a revision of Porella in the Korean Peninsula based mostly on a study of the collections housed in the herbaria of Jeonbuk National University (JNU) using an integrative approach to systematize the liverwort, as well as a study of the types of several species and available literature sources. In total, 17 species were recorded, including six taxa (Porella acutifolia ssp. tosana, P. platyphylla, P. perrottetiana, P. pinnata, P. spinulosa, and P. subobtusa) whose identities were not confirmed with the available materials and were suspected to be recorded by mistake. Two species are described as new to science. Porella koreana sp. nov. is morphologically similar to P. caespitans and P. densifolia; however it has an acute apex, and cells in the middle of the dorsal lobe have convex trigones. Porella chulii sp. nov. is somewhat morphologically similar to P. japonica; however, it has a dorsal leaf lobe margin that is slightly incurved, and the cells in the middle of the dorsal lobe are 20–25 μm in size. Each confirmed species is annotated by morphological descriptions based on available Korean material, data on ecology, its distribution, specimens examined, and illustrations. The identification key for Porella taxa known in Korea is provided.